Adsorptive behavior of multi-walled carbon nanotubes immobilized magnetic nanoparticles for removing selected pesticides from aqueous matrices. (June 2023) - Pereira, Hercules A.; da Boit Martinello, Kátia; Vieira, Yasmin; Diel, Júlia C.; Netto, Matias S.; Reske, Gabriel D.; Lorenzett, Ezequiel; Silva, Luis F.O.; Burgo, Thiago A.L.; Dotto, Guilherme Luiz
Abstract: The present work synthesized two new materials of functionalized multi-walled carbon nanotubes (MWCNT–OH and MWCNT–COOH) impregnated with magnetite (Fe3 O4 ) using solution precipitation methodology. The resulting MWCNT–OH–Mag and MWCNT–COOH–Mag materials were characterized by scanning electron microscopy coupled with energy dispersion X-ray spectroscopy, Fourier transform infrared, X-ray diffraction, atomic force microscopy, and electrical force microscopy. The characterization results indicate that the –OH functional groups in the MWCNT interact effectively with magnetite iron favoring impregnation and indicating the regular distribution of nanoparticles on the surface of the synthesized materials. The adsorption efficiency of the MWCNT–OH–Mag and MWCNT–COOH–Mag materials was tested using the pollutants 2, 4-D and Atrazine. Over batch studies carried out under different pH ranges, it was found that the optimal condition for 2, 4-D adsorption was at pH 2, while for Atrazine, it was found at pH 6. The rapid adsorption kinetics of 2, 4-D and Atrazine reaches equilibrium within 30 min. The pseudo-first-order model described 2, 4-D adsorption well. The General-order model described better atrazine adsorption. The magnetically doped adsorbent functionalized with –OH surface groups (MWCNT–OH–Mag) demonstrated superior adsorption performance and increased Fe-doped sites. The Sips model described the adsorption isotherms accurately. MWCNT–OH–Mag presented the greatest adsorption capacity at 51.4 and 47.7 mg g −1 for 2, 4-D and Atrazine, respectively. Besides, electrostatic forces and complexation rule the molecular interactions between metals and pesticides. The leaching and regeneration tests of the synthesized materials indicate high stability in an aqueous solution. Furthermore, experiments with wastewater samples contaminated with the model pollutants indicate that the novel adsorbents are highly promising for enhancing water purification by adsorptive separation. Graphical abstract: Image 1 Highlights: Immobilization of magnetite particles in functionalized multi-walled nanotubes. Carbon nanotubes with OH groups interact with Fe more effectively than the COOH. Application of iron-impregnated multi-walled nanotubes to remove pesticides from water. Metallic impregnation optimizes the adsorption of 2, 4-D and atrazine pesticides. An inedited molecular approach was proposed.